New Trends in High Voltage Engineering - Shariatinasab, Reza (IntechOpen, 2018)
For public access to electric energy, exploitation of high-voltage networks is inevitable. Meanwhile, high-voltage engineering plays a basic role in designing and operating network insulation. On the other hand, modern high-voltage engineering trends are developing environmentally friendly and recyclable insulators. Recently, nano-doping of environmentally friendly polypropylene/inorganic nano-composites has shown improvement to its characteristics and increased the use of HVDC insulation. In this book, research is carried out on nano-doping effects on the performance and future development of polypropylene nano-composites. Also, the characteristics of CF3I gas and its combination with nitrogen by experimental results are investigated. Installation of capacitors may result in voltage increment at the point where the capacitors are connected to the network. This issue is important when a harmonic resonance has occurred. The harmonic resonances may lead to voltage stress on the power network insulation. The book also discusses the effect of harmonic resonance on the insulation.